Turkish adaptation of Young's Internet Addiction Test-Short Form: a reliability and validity study on university students and adolescents - Kutlu, Mustafa; Savci, Mustafa; Demir, Yasin; Aysan, Ferda (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2016)
Objective: The objective of the study is to examine the validity and reliability of the Turkish version of the Short Form of Young's Internet Addiction Test (YIAT-SF) for university students and adolescents. Methods: The study was conducted with four different sample groups of 1167 university students of 17-35 years of age and five different sample groups of 945 adolescents aged between 14 and 17. The validity of the scale was examined using exploratory factor analysis, confirmatory factor analysis and criteria-dependent validity. The reliability of the scale was analyzed using Cronbach alpha coefficient and test-retest method. Item analysis was conducted using corrected item total points correlation and item average points for 27% of top and bottom groups. Findings: Exploratory factor analysis results demonstrated that the scale was formed by 12 items and a single factor for both university students and the adolescents; and confirmatory factor analysis showed that YIAT-SF had good adaptive values for both groups and correlation analysis results determined that YIAT-SF was correlated with the applied scales within the context of criteria-dependent validity for both university students and the adolescents. Both YIAT-SF Cronbach's alpha and test-retest reliability coefficients were found to be within the acceptable range for both groups. Finally, corrected item total correlation coefficients were observed to be at acceptable levels for both university students and the adolescents and t-values related to item average points for 27% of top and bottom groups were found to be significant. Result: These findings demonstrated that YIAT-SF is a reliable and valid scale for both university students and adolescents.
Young internet bağımlılığı testi kısa formunun türkçe uyarlaması: Universite öğrencileri ve ergenlerde geçerlilik ve güvenilirlik çalışması
Keywords: internet addiction; adolescent; university student; validity; reliability; exploratory factor analysis; confirmatory factor analysis